Rare Rubrics from Different Repertories Related to Acute Suppurative Otitis Media (ASOM). (Homoeopathy for All, 2022)
Repertory is a tool which cut short the human labour, by using repertory one can easily get a narrow range of similar medicine and similimum can be prescribed after confirming with material medica. Also, in acute cases, one could perfectly prescribe using repertorial approach. Various homoeopathic literature were reviewed and critically analysed including repertories like, Synthesis Repertory1, Repertory of the Homoeopathic Materia Medica by J.T Kent2, Murphy Repertory3, Boger Boenninghausen’s Characteristics & Repertory4.
Keywords: ASOM; Repertory; Rubrics